Struvite recovery from human urine in inverse fluidized bed reactor and evaluation of its fertilizing potential on the growth of Arachis hypogaea. Issue 1 (February 2021) - Sathiasivan, Kiruthika; Ramaswamy, Jeyalakshmi; Rajesh, Mathur
Abstract: Nutrients, nitrogen and phosphorus, present in wastewater need to be removed to protect water bodies from the consequences of eutrophication. Among the many possibilities, recovering the nutrients as struvite has become attractive, particularly from the isolated sources of urine stream considering its potential use as a fertilizer akin to Diammonium phosphate (DAP). The present paper deals with studies on the production of struvite from synthetic human urine using an inverse fluidized bed reactor (IFBR) based on the batch process results. Unlike the 85% recovery of struvite for the optimized molar ratios of magnesium, ammonium and phosphate at pH 9.5, the IFBR experiments yielded approximately 95% recovery at optimal operating parameters with respect to condition, size of low density polypropylene particles (6 mm) with density (963 kg/m 3 ) and bed height (45 cm). The purity and microstructure were examined using XRD, SEM / EDS, and Raman spectroscopy. The fertilization efficiency was assessed with struvite application and integrated with nitrogen-fixing Azospirullum rhizobium and phosphate-solubilizing Bacillus megaterium on the growth of Arachis hypogaea plants in the field. Studies conducted along with commonly used DAP on sandy topsoil indicated efficient absorption of struvite by microbes and providing the most encouraging number of seed/pod (capsule) and straw yields (g/plant) comparable to conventional superphosphate DAP. The nutrient availability in the soil was confirmed based on the soil properties before and after harvest. Extensive tests of the plant properties proved the positive agronomic results of struvite fertilization. Graphical Abstract: ga1 Highlights: Struvite production using IFBR with 95% P-recovery is economically efficient. Lower minimum fluidization velocity with less energy using low - density particles. Integrated nutrient management of struvite with bio fertilizers has been demonstrated. Plant reaction in terms of growth, yield, biomass, and soil P were assessed. Significant benefits for agronomy due to the synergistic effect of P and Mg uptake.